2008
DOI: 10.1037/1076-8998.13.4.345
|View full text |Cite
|
Sign up to set email alerts
|

Working in the sky: A diary study on work engagement among flight attendants.

Abstract: This study aims to gain insight in the motivational process of the Job Demands-Resources (JD-R) model by examining whether daily fluctuations in colleague support (i.e., a typical job resource) predict day-levels of job performance through self-efficacy and work engagement. Forty-four flight attendants filled in a questionnaire and a diary booklet before and after consecutive flights to three intercontinental destinations. Results of multilevel analyses revealed that colleague support had unique positive effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

35
356
5
12

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 405 publications
(423 citation statements)
references
References 58 publications
35
356
5
12
Order By: Relevance
“…However, several longitudinal studies have shown that psychological capital (Luthans, 2002), consisting of self-efficacy, optimism, resilience, and hope, was positively related to work engagement among employees (Avey et al, 2010) and students (Ouweneel et al, 2011). On a daily basis, optimism, self-esteem, and self-efficacy were significantly related to work engagement (Tims et al, 2011;Xanthopoulou et al, 2008Xanthopoulou et al, , 2009a. In the present study, we focus on the engaging value of another dimension of psychological capital, namely hope, on a daily basis.…”
Section: Building Towards Engagementmentioning
confidence: 99%
See 3 more Smart Citations
“…However, several longitudinal studies have shown that psychological capital (Luthans, 2002), consisting of self-efficacy, optimism, resilience, and hope, was positively related to work engagement among employees (Avey et al, 2010) and students (Ouweneel et al, 2011). On a daily basis, optimism, self-esteem, and self-efficacy were significantly related to work engagement (Tims et al, 2011;Xanthopoulou et al, 2008Xanthopoulou et al, , 2009a. In the present study, we focus on the engaging value of another dimension of psychological capital, namely hope, on a daily basis.…”
Section: Building Towards Engagementmentioning
confidence: 99%
“…Namely, positive emotions build proactivity (Fritz and Sonnentag, 2009), and resources like optimism and self-efficacy have been found to predict work engagement (Tims et al, 2011;Xanthopoulou et al, 2008Xanthopoulou et al, , 2009a. Recently, Salanova et al (2011) showed that positive emotions such as enthusiasm, satisfaction, and comfort predict work and task engagement.…”
Section: Building At a Daily Levelmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, work engagement represents employees' attitudes towards work and the extent of involvement to which they are willing to commit (Kahn, 1990). Accordingly, when engaged, employees feel a sense of involvement in their work mentally, intellectually and physically, and they are eager to exercise all of their dynamism at work (Xanthopoulou, Bakker, Heuven, Demerouti, & Schaufeli, 2008). In contrast, non-engaged employees have low levels of ambition for their job in physical terms, and they lack an emotional connection with their colleagues (Kahn, 1990).…”
Section: Transformational Leadership and Work Engagementmentioning
confidence: 99%